NON-ADHERENCE TO ANTI-DIABETIC MEDICATIONS AMONG DIABETES PATIENTS ATTENDING DIABETES CLINIC AT KISENYI HEALTH CENTER IV, KAMPALA DISTRICT, A Cross-Sectional STUDY. - Bahangondi, Richard; Mpamize, Habert; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student's Journal of Health Research Africa, 2025)
Background Non-adherence to anti-diabetic medications among diabetes patients poses significant challenges to effective diabetes management, yet many patients fail to take their medications consistently. This study aimed to identify socio-economic, individual, and health facility factors contributing to non-adherence to anti-diabetic medications among diabetes patients attending the diabetic clinic at Kisenyi Health Center IV. Methodology A descriptive cross-sectional study design was used, involving 30 diabetes patients selected through simple random sampling. Data was collected using structured questionnaires, and analysis involved descriptive statistics to assess the influence of various factors on medication adherence, with results presented in the form of figures, tables, and pie charts. Results The study involved more males, 25 (83%), than females, 5 (17%), the majority of whom were aged between 31 to 45 years, and the least, 1(3%), were aged 61 and above. Findings indicated that socio-economic factors, including limited income (73%) and unemployment (80%), negatively affected adherence. Individual factors such as forgetfulness (57%) and concerns about side effects (80%) contributed to non-adherence. Health facility-related factors, including long waiting times (70%) and limited availability of follow-up appointments (80%), further discouraged adherence among patients. Additionally, 53% reported insufficient patient education programs, which negatively influenced adherence. Conclusion There was a complex interplay of socioeconomic, individual, and health facility-related factors contributing to this issue, including medium household income, proximity to the health facility, infrequent transportation problems, forgetfulness, and experiencing side effects that negatively affected adherence. Recommendation Enhanced patient education, improved patient-provider communication, and efficient clinic management practices to mitigate barriers to adherence and support diabetes management at Kisenyi Health Center IV.